2019
DOI: 10.1071/fp18189
|View full text |Cite|
|
Sign up to set email alerts
|

In silico characterisation and functional validation of chilling tolerant divergence 1 (COLD1) gene in monocots during abiotic stress

Abstract: The G protein-coupled receptor is one of the major transmembrane proteins in plants. It consists of an α subunit, a β subunit and three γ subunits. Chilling tolerant divergence 1 (COLD1) includes a Golgi pH receptor (GPHR) domain, which maintains cell membrane organisation and dynamics, along with abscisic acid linked G protein-coupled receptor (ABA_GPCR) that regulates the signalling pathways during cold stress. In the present study, we performed characterisation of a homologous COLD1 from the economically im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Sugarcane wild relative Erianthus arundinaceus is a potential crop for the production of high biomass and reservoir of many genes related to agronomic, biotic and abiotic stresses. We have isolated and characterized many genes from E. arundinaceus 14 , 15 , 19 22 and many of genes are still unexplored. Besides, transcriptome studies were reported for many traits such as cold transcriptome 23 , sucrose 24 , agronomic traits 25 , lignin 28 , red stripe disease 26 , smut disease 27 except for salinity stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugarcane wild relative Erianthus arundinaceus is a potential crop for the production of high biomass and reservoir of many genes related to agronomic, biotic and abiotic stresses. We have isolated and characterized many genes from E. arundinaceus 14 , 15 , 19 22 and many of genes are still unexplored. Besides, transcriptome studies were reported for many traits such as cold transcriptome 23 , sucrose 24 , agronomic traits 25 , lignin 28 , red stripe disease 26 , smut disease 27 except for salinity stress.…”
Section: Discussionmentioning
confidence: 99%
“…Introgression of many genes from E. arundinaceus into sugarcane through conventional and biotechnological approaches has improved the agronomic performance of sugarcane varieties 17 , 18 . We have isolated, characterized, and overexpressed many genes from E. arundinaceus such as heat shock protein 70 14 , 19 , DREB2 20 , glyoxalase gene 15 , α-expansin 1 21 and chilling tolerant divergence 1 (COLD1) gene 22 , which shows the genetic importance of E. arundinaceus in improving the tolerances to biotic and abiotic stresses in sugarcane . There were several RNASeq studies in sugarcane for many traits such as agronomic traits, cold stress, sucrose, lignin, red stripe and smut disease except for salinity tolerance 23 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative real-time PCR (qRT-PCR) analysis was conducted using the StepOne real-time PCR system (Applied Biosystems, Burlington, ON, Canada). Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was used as an endogenous reference control [30][31][32][33][34][35][36][37]. The qRT-PCR profile was as follows: 10 min of denaturation at 95 • C, followed by 40 cycles 15 s of denaturation at 95 • C, 1 min of annealing and extension at 60 • C in a final volume of 25 µL reaction [26,29,30].…”
Section: Quantitative Rt-pcr Analysismentioning
confidence: 99%
“…To perform qRT-PCR experiments, the cDNA converted using total RNA isolated from root samples of drought-stressed and control plants were used as a template. qRT-PCR was performed on a Step-One Plus Real-Time PCR system (Applied Biosystems, Canada) by following the method explained elsewhere (Anunanthini et al 2019;Manoj et al 2019;AswinNarayan et al 2019;Dharshini et al 2020aDharshini et al , 2020bSwathik Clarancia et al 2020). Each reaction was carried out in triplicates.…”
Section: Relative Expression Analysismentioning
confidence: 99%